Dialogowość, literatura i wolność słowa - Płuciennik, Jarosław (Przestrzenie Teorii, 2008)
A point of departure in my article is Francesco Loriggio's brilliant analysis Mind as Dialogue: The Bakhtin Circle and Pragmatist Psychology. My essay stands as a polemics with one of the main theses of Loriggio that dialogics should be divided into just two kinds: novelistic and theatrical one. I propose a more historical approach to the development of dialogics. In different cultural areas various practices and theories may form themselves in divergent ways. Since 1 7,h century, the development of the dialogics traveled from an apocalyptic - and demonizing its opponents - discourse (John Milton's approach in Areopagitica), through dialogics of cooperation of obligations and laws (Polish Socinians, especially Jan Crell), dialogics of deduction (transcendental cooperation in I. Kant), through the dynamic dialogics of induction and creativity (John. S. Mill) to the dynamic fuzzy and multi-valued dialogics of a concept of rationality in R. Rorty or the theory of (un)free speech in S. Fish. Dialogics is not represented merely by two discoursive practices. I postulate existence of at least one medium discourse: deliberative rhetoric.